Triple HIV-1 Infection Is Associated With Faster CD4+ T-Cell Decline - Zhang, Yu; Su, Bin; Li, Hanping; Han, Jingwan; Zhang, Tong; Li, Tianyi; Wu, Hao; Wang, Xiaolin; Li, Jingyun; Liu, Yongjian; Li, Lin (Frontiers in Microbiology, 2020)
HIV-1 dual infection occurs when an individual is simultaneously or sequentially infected with two or more genetically distinct HIV-1 strains. According to the number of infected strains, HIV-1 dual infection can be divided in double infection and triple infection and so on. Currently, the majority of dual infection cases have been reported to be double infections which can result in detrimental clinical outcomes. The high incidence of double infection among specific high-risk populations increases the likelihood of triple infection, which has been sporadically described. There is no doubt that we are concerned about the association between triple infection and disease progression. However, this relationship is still unclear on the population level. In this study, 70 individuals from the Beijing PRIMO cohort were longitudinally followed up with a median time of 15.75 months for the purpose of investigating the incidence of dual infection. Phylogenetic analyses using bulk and single-genome sequences showed that 9 individuals acquired double infection, with the incidence of 9.21 per 100 person-years, and 3 individuals with triple infection were identified, with the incidence of 3.07 per 100 person-years. The further survival analysis demonstrated that the triple infection group exhibited faster CD4+ T-cell decline. In summary, these results demonstrate for the first time that the triple HIV-1 infection might reduce CD4+ T-cell counts, which would predict a more rapid disease progression.